2021
DOI: 10.2147/cia.s318857
|View full text |Cite
|
Sign up to set email alerts
|

Development and Validation of 3-Month Major Post-Stroke Depression Prediction Nomogram After Acute Ischemic Stroke Onset

Abstract: The early detection of major post-stroke depression (PSD) is essential to optimize patient care. A major PSD prediction tool needs to be developed and validated for early screening of major PSD patients. Patients and Methods: A total of 639 acute ischemic stroke (AIS) patients from three hospitals were consecutively recruited and completed a 3-month follow-up. Sociodemographic, clinical and laboratory test data were collected on admission. With major depression criteria being met in the DSM-V, 17-item Hamilton… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 44 publications
0
6
0
Order By: Relevance
“… 27 , 28 , 29 PSD after lacunar and non-lacunar stroke shared some common risk factors, such as female gender, degrees of neurological deficits and functional outcome, which had been studied and identified as the predictors of PSD for a series of studies. 29 , 30 , 31 , 32 , 33 , 34 Meanwhile, there were also some risk factors associated with PSD after lacunar stroke and non-lacunar stroke differently. For example, the unfavorable treatment effect was associated with PSD after lacunar stroke more strongly.…”
Section: Discussionmentioning
confidence: 98%
“… 27 , 28 , 29 PSD after lacunar and non-lacunar stroke shared some common risk factors, such as female gender, degrees of neurological deficits and functional outcome, which had been studied and identified as the predictors of PSD for a series of studies. 29 , 30 , 31 , 32 , 33 , 34 Meanwhile, there were also some risk factors associated with PSD after lacunar stroke and non-lacunar stroke differently. For example, the unfavorable treatment effect was associated with PSD after lacunar stroke more strongly.…”
Section: Discussionmentioning
confidence: 98%
“…Post-stroke hypertension and higher diastolic blood pressure on post-stroke physical examination were associated with PSD in our predictive models. One prior study demonstrated that hypertension plays a role in predicting 3-month PSD ( 37 ). Another study reported that a longer duration of hypertension was also associated with new-onset depression after stroke ( 38 ).…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, this study developed a prediction model for the individualized risk of behavioral problems in children with TD, and a nomogram was plotted for the prediction model. To date, the application of a nomogram to predict the risk of TD with behavioral problems is lacking, although nomograms have been widely used as a reliable clinical tool to create a simple intuitive graph to quantify the risk of a clinical event of interest in other diseases [ 19 , 20 ]. In the present study, the model based on age, abnormal birth history, parenting pattern, family history, TD type and tic severity had a significant predictive performance for behavioral problems in children with TD.…”
Section: Discussionmentioning
confidence: 99%